Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae) - Ortega-Salas, Héctor (Zootaxa, 2018)
Erpetogomphus oxybelis sp. nov. is described and figured from Río Hondo, Veracruz State, Mexico (18.387 N, -96.174 W, 20 m a.s.l.), the holotype is deposited in the Frost Entomological Museum at Pennsylvania State University, USA [PSUC]. Relationship with members of the ophibolus group sensu Garrison are discussed.